FAKTOR-FAKTOR YANG MEMENGARUHI FINANCIAL DISTRESS PADA PERUSAHAAN SUBSEKTOR TELEKOMUNIKASI PERIODE 2016-2023 - ARILYN, ERIKA JIMENA; IMTIYAZ, FATHARANI ZAHRA (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
This study aims to examine the factors affecting financial distress in telecommunication subsector companies listed on the Indonesia Stock Exchange from 2016 to 2023. Specifically, the research investigates the impact of liquidity, leverage, profitability, firm size, and free cash flow on financial distress. The study addresses the need to understand these factors to help companies and investors anticipate financial risks. Using quantitative methods, this research utilizes secondary data collected from annual financial reports of telecommunication companies. A purposive sampling technique is applied to select companies that meet specific criteria, such as consistent financial reporting in Indonesian Rupiah. Data analysis is conducted through logistic regression, which includes descriptive statistics, model testing, and hypothesis testing. The result indicates that leverage, profitability, and free cash flow effects the financial distress, while liquidity and firm size do not. These findings both confirm and contrast the previous studies, enriching the existing discourse on financial distress factors. The study offers valuable insights for corporate management and investors in their efforts to mitigate financial distress in the telecommunication sector